Recent developments on the application of molecular probes in multiple myeloma: Beyond [18F]FDG - Zhang, Shaojuan; Shang, Jingjie; Ye, Weijian; Zhao, Tianming; Xu, Hao; Zeng, Hui; Wang, Lu (Frontiers in Bioengineering and Biotechnology, 2022)
Multiple myeloma (MM) is a neoplastic plasma cell proliferative disorder characterized by multiple osteolytic bone destruction as a radiological morphological marker. Functional imaging, particularly nuclear medicine imaging, is a promising method to visualize disease process before the appearance of structural changes by targeting specific biomarkers related to metabolism ability, tumor microenvironment as well as neoplastic receptors. In addition, by targeting specific antigens with therapeutic antibodies, immuno-PET imaging can support the development of personalized therangostics. At present, various imaging agents have been prepared and evaluated in MM at preclinical and clinical levels. A summary overview of molecular functional imaging in MM is provided, and commonly used radiotracers are characterized.